Legisladores, captadores e assistencialistas: A representaç\~ao política no nível local - Acir Almeida; Felix Lopez (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper describes and analyses political representation at the local level, with emphasis on the representative's choice between adopting clientelistic or universalistic practices. Based on a non-representative sample of 112 local representatives from twelve municipalities of Minas Gerais, we identify three distinct types of representative: the legislator, who dedicates himself to the formal functions of the mandate; the fundraiser, who gives priority to meeting voters' collective requests; and the assistencialist, who gives priority to meeting particularistic requests. The results from a Multinomial Logit regression model of the type of representative suggest that the probability of a representative engaging in assistencialism is conditioned by demographic, socioeconomic, political and cultural factors, thus corroborating several hypothesis from the literature on political clientelism.
Keywords: Z00; 330; political representation; clientelism; local politics